Metastasis from Penile Squamous Cell Carcinoma to Brain: A Case Report and Review of Literature - Hanish Bansal; Ashwani Chaudhary; Dipesh Batra; Rohit Jindal (Indian Journal of Neurosurgery)
We report a very rare case of a 63-year-old man with penile carcinoma who developed brain metastasis. Brain metastasis from penile carcinoma is very rare, and only six cases have been reported so far as per our literature review. In view of controlled primary tumor and absence of systemic disease, tumor was excised and the patient remained clinically controlled till 3 months after follow-up.